Pseudo Swarm Implementation Using Robotic Agents and Graphical Simulation - Aboganda, Jeremiah C (Archīum Ateneo, 2010)
The Pseudo Swarm Implementation aims to demonstrate the concept of swarm intelligence through the use of simulation and actual robotic units in hopes of recreating the complexity of natural systems. The actual swarm robots are modular in design and powered by PIC16f84 microprocessors. Each robot is composed of the motor module and a detachable sensor module. The motor module was constructed first and designed to handle basic movement and the random walk function. The sensor module was then designed afterwards which is capable of interfacing with the motor module through a universal protocol. The simulation platform was accomplished through the use of ActionScript3 to graphically depict the swarm behaviors given certain rules and a controlled environment. The simulation’s purpose is to complement the data by creating robot objects similar to the actual robots and reproducing a larger number of them in a given environment. This work is a comprehensive study on a variation of the of swarm intelligence implementation of how a complex system may be composed of simple units defined by basic state machines.